2016
DOI: 10.3390/ijms17050791
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Biomarkers in Biliary Tract Cancers

Abstract: Biliary tract cancers (BTCs) are a group of highly aggressive malignant tumors with a poor prognosis. The current diagnosis is based mainly on imaging and intraoperative exploration due to brush cytology havinga low sensitivity and the standard markers, such as carcinoembryonic antigen (CEA) and carbohydrate 19-9 (CA19-9), not having enough sensitivity nor specificity to be used in a differential diagnosis and early stage detection. Thus, better non-invasive methods that can distinguish between normal and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 209 publications
(282 reference statements)
0
23
0
5
Order By: Relevance
“…отиди, що регулюють експресію генів на посттранс-крипційному рівні шляхом РНК-інтерференції [16][17][18][19][20]. За офіційними даними проекту Енцикло-педії елементів ДНК (GENCODE) Консорціуму міжнародного співробітництва дослідницьких груп, на сьогодні відомо 2588 мікро-РНК людини та при-близно 60 % білок-кодуючих генів, що є мішенями для мікро-РНК [21].…”
Section: ключові слова: мікро-рнк; захворювання біліарної системи; урunclassified
See 1 more Smart Citation
“…отиди, що регулюють експресію генів на посттранс-крипційному рівні шляхом РНК-інтерференції [16][17][18][19][20]. За офіційними даними проекту Енцикло-педії елементів ДНК (GENCODE) Консорціуму міжнародного співробітництва дослідницьких груп, на сьогодні відомо 2588 мікро-РНК людини та при-близно 60 % білок-кодуючих генів, що є мішенями для мікро-РНК [21].…”
Section: ключові слова: мікро-рнк; захворювання біліарної системи; урunclassified
“…Ре-зультат реалізації дії зрілої мікро-РНК в RISC за-лежить від того, з якою нетрансльованою ділянкою цільової матричної РНК (мРНК) відбувається вза-ємодія (рис. 2) [17,20,27].…”
Section: механізм дії мікро-рнкunclassified
“…DNA-PKcs and Ku70 are tumor suppressors, and loss of DNA-PKcs and Ku70 expression is an important biological marker for metastasis, invasion, and prognosis of GBC [55]. It has been reported that the aberrant nucleoside levels in the plasma, urine, bile, and tissues served as biomarkers in the diagnosis and these nucleosides may be as useful as biological markers for gallbladder cancer [56]. The positive β2M expression or loss of ATP5B expression in tumor tissues is closely related to the metastasis, invasion, and poor-prognosis of gallbladder cancer [57].…”
Section: Soxmentioning
confidence: 99%
“…Therefore, circulating miRNAs may be noninvasive and specific diagnostic and/or prognostic molecular biomarkers for human diseases, including cancer [4, 7, 58, 59]. In BTCs, many circulating miRNAs seem to be reproducible and reliable potential biomarkers as well as possible therapeutic targets [60]. Table 2 summarizes the circulating miRNAs with potential diagnostic, prognostic, and predictive biomarker applications in BTCs.…”
Section: Circulating Mirnas As Potential Btcs Biomarkersmentioning
confidence: 99%